A Spicy Mystery, or ... with soap on our hands and foam at our mouths ... - Saberi, Helen J; Helou, Anissa; Pombo-Villar, Esteban (Petits Propos Culinaires, 1994)
The newly formed international organization INTERSPI, the young sister of INTERPOL, but dedicated to intercontinental investigations of mystery spices (or spicy mysteries), has scored its first triumph in (more or less) identifying a spice which has eluded the attention of all previous English-language cataloguers of spices. Detective Saberi (daughter of a former Chief Inspector of Police in the City of York, author of Noshe Djan- Afghan Food and Cookery, and currently working with Alan Davidson on The Oxford Companion to Food) inaugurated the enquiry, as she explains in this report (sequential in construction, to expose her modus operandi), but found that the scale of the operation called for international cooperation. The co-investigators whom she enlisted are named above. They were shrewdly chosen. Anissa Helou is the author of the forthcoming (September 1994) Lebanese Cuisine (Grub Street, London). Dr Pombo-Villar, who runs his part of INTERSPJ from a base in Switzerland, is a chemist with a particular interest in spices. Each of the authors speaks in turn. Detective Saberi then invites the Project Coordinator to review the somewhat perplexing results of the enquiry and to indicate the course of the further investigations which the whole team believe must be made. All help to this end will be welcome.